The Future of Health, Wellbeing and Physical Education Optimising Children's Health through Local and Global Community Partnerships - Lynch, Timothy (Springer International Publishing : Imprint: Palgrave Macmillan, 2016)
This book uses the example of a partnership journey between universities, schools, the local health industry as well as a number of government organisations which worked to ensure the growth of physical education in primary education. The initiative employed the United Nations (UN) ideals as a model and contextualised them within local schools and communities. What began as a pathway seed quickly grew to involve multi-stakeholder partnerships and therefore explores how the UN Sustainable Development Goals (SDG) may be implemented at a grass roots level. Tim Lynch is Lecturer in Primary Physical Education at Plymouth University, UK. He has been involved in early years/ primary, secondary and higher education for 22 years as a classroom teacher, Head teacher, Health and Physical Education (HPE) specialist and Teacher Educationalist, working in various national and international school communities, education systems and institutions. Tim is the Vice-President for Oceania for the International Council for Health, Physical Education, Recreation, Sport and Dance (ICHPER-SD).